2006
DOI: 10.1111/j.1398-9995.2006.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climatic change in children with atopic eczema

Abstract: The change from a subartic/temperate to a subtropical climate for 4 weeks improved significantly skin symptoms (SCORAD) and quality of life, even for 3 months after return.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 30 publications
5
39
0
7
Order By: Relevance
“…Nevertheless, a randomized trial of Norwegian children with atopic eczema demonstrated significant improvements after 4 weeks in a sunny climate [26]. Further, an observational study in 2007 of Spanish asthmatic children revealed that health related quality of life was highest in summer and lowest in autumn [60].…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…Nevertheless, a randomized trial of Norwegian children with atopic eczema demonstrated significant improvements after 4 weeks in a sunny climate [26]. Further, an observational study in 2007 of Spanish asthmatic children revealed that health related quality of life was highest in summer and lowest in autumn [60].…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…First, it facilitates conversion of transurocanic acid, a breakdown product of filaggrin, into the cis-urocanic acid isoform that has immunosuppressive effects [45]. Moreover, UVA and UVB may suppress superantigen production by S. aureus [83]. UVB also stimulates cutaneous synthesis of previtamin D from 7-dehydrocholesterol.…”
Section: 42mentioning
confidence: 99%
“…Yet, until recently, there was little evidence to support this notion. One study found that relocating children with AD from the home subarctic/temperate climate of Norway to a subtropical climate in Gran Canary for 4 weeks improved skin symptoms and quality of life [3,[83][84][85][86][87][88]. The climate in a given geographic location is determined by a combination of multiple factors, including temperature, humidity, and precipitation, as well as related factors, such as ultraviolet (UV) exposure.…”
Section: Climatementioning
confidence: 99%
“…A significant reduction in clinical signs and symptoms, an improvement in the quality of life index, and reduced use of topical corticosteroids was observed in the children that moved into a tropical zone after 4 weeks and 3 months (p<0.0005) [54]. The study results suggest that enough doses of UVB radiation to generate sufficient vitamin D synthesis have the potential to treat AD.…”
Section: A Study By Vahavihu Et Al Demonstrated That 17 Patients (94mentioning
confidence: 59%
“…Byremo et al [54] conducted a study in which 30 randomly selected children from 4-13 years of age with severe AD in Norway (subarctic/temperate climate) moved into a tropical zone for 4 weeks and the other 26 children remained in Norway, then were followed up for 3 months. A significant reduction in clinical signs and symptoms, an improvement in the quality of life index, and reduced use of topical corticosteroids was observed in the children that moved into a tropical zone after 4 weeks and 3 months (p<0.0005) [54].…”
Section: A Study By Vahavihu Et Al Demonstrated That 17 Patients (94mentioning
confidence: 99%